Disaster governance, energy insecurity, and public health in rural Puerto Rico: how communities resist political abandonment - Sergio Rivera-Rodríguez; Adrian Santiago-Santiago; Sheilla R-Madera; Mark Padilla; Nelson Varas-Díaz; Kariela Rivera-Bustelo; Claudia Mercado-Rios; John Vertovec; Arturo Massol-Deyá; Jeffrey Ramos; Genevieve Reid; Rebecca Rodríguez-Banch; et al. (Frontiers in Public Health, 2025)
Puerto Rico, an unincorporated US territory, faces systemic governmental neglect that disproportionately affects public health, particularly in the wake of disasters. Systemic patterns of political corruption, and post-disaster mismanagement, rooted in colonial governance, have shaped PR’s longstanding vulnerability reflecting in frequent power outages and energy delays. This study examines political abandonment feelings in Puerto Rico through the lens of energy insecurity and disaster governance, focusing on the rural municipality of Adjuntas. Using Atiles’ framework of Normalization of Exceptionality and (In)Security, we investigate how state inaction, privatization, and bureaucratic inefficiencies perpetuate vulnerability in disaster-prone communities. Using qualitative in depth-interviews with Adjuntas’ residents living with chronic conditions (n = 45) and stakeholders (n = 15), we explore the impact of political abandonment in energy instability. We employed thematic analysis to identify patterns and themes within the dataset. We focus on three primary themes: feelings of political abandonment, political corruption, and community response. Many participants expressed feeling abandoned by the government, particularly in the wake of energy crises and disaster recovery failures. Our findings reveal that political abandonment is not merely a failure of governance but an intentional strategy that limits recovery efforts and sustains structural inequalities. The privatization of PR’s electrical grid has exacerbated disparities, reinforcing patterns of disaster capitalism. Casa Pueblo, a community organization, demonstrate community-driven resilience, offering a model of decentralized energy solutions that counteract state neglect. These findings contribute to broader discussions on disaster governance, energy justice, and health disparities.